Physical, Chemical, and Sensory Characteristics of Frozen Salted Edamame During Storage at Room Temperature - Winda Amilia; Andi Eko Wiyono; Dhifa Ferzia; Andrew Setiawan Rusdianto; Ida Bagus Suryaningrat; Nidya Shara Mahardika; Bertung Suryadarma (Food, Agriculture and Natural Resources - NETWORKS, 2021)
Edamame soybeans are a superior product in Jember Regency. Edamame has the advantage of protein, calcium and iron content. In general, edamame soybeans are a perishable food commodity that must be processed immediately. One of the processed edamame products is frozen salted edamame which is a practical ready-to-eat snack. Frozen salted edamame has attracted the interest of the people of Jember and people outside the city. This product is popular with people outside the city, so they often buy it to take home as a souvenir from Jember Regency. Uncontrolled environmental conditions during the trip with sudden temperature changes without cold storage cause the potential for physical damage or deterioration of quality in frozen salted edamame. Therefore, further observations are needed to determine changes in the quality of frozen salted edamame products during the trip without cold storage at room temperature storage. The purpose of this study was to determine the effect of room temperature storage time on physical quality, chemical quality, and organoleptic quality of frozen salted edamame products. The design of this study used a completely randomized design with a single factor, namely five treatments for different durations (0 hours, 12 hours, 24 hours, 36 hours, and 48 hours after removed from the freezer). The analyzes carried out in this study were the test of texture, color, pH, total dissolved solids, total acid, antioxidant activity, moisture content, and organoleptics. The results showed that the frozen salted edamame product decreased during storage time at room temperature. Based on the results of research, the duration of storage for frozen salted edamame products at room temperature has an effect on the value of color, pH, total dissolved solids, total acid, and water content, but does not affect the texture and antioxidant activity. The quality of the product also decreased in color, taste, aroma, and texture attributes.